An Improvement of Ant Colony Adhoc On-Demand Vector (ANT-AODV) with K-Means Clustering Nodes Method in Mobile Adhoc Network (MANET) Environment - Dimas W.L. Pamungkas; Radityo Anggoro (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Nahdlatul Ulama Blitar, 2021)
MANET (Mobile Ad hoc Network) is a technology used for data communication on mobile media. MANET moves and speeds also randomly with different distances between nodes. In the AODV reactive protocol, the development of a routing protocol with an ant colony model can significantly improve performance. The measurement results will impact the decision on the development of the ant colony protocol implemented in AODV to obtain the best route for data transmission. Several studies have developed the K-Means clustering method to obtain the shortest and best route from the AODV protocol. It does not measure congestion, distance, energy, and signal strength of the wireless network. In this research, a combination of methods was carried out, by combining clustering and also ant colony method to get the best route while dealing with the problems that have been mentioned. Implementation is done by modifying the AODV protocol and adding the two methods. At the end of the research, metric measurements were carried out to determine the Packet Delivery Ratio, End to End Delay and also the Average Hop Count.